The Influence of Job Achievement, Work Experience and Performance Evaluation on Employee Position Promotion in the Regional Energy and Mineral Resources Department of North Sulawesi Province - Putri, Nabila N. Yusuf; Tumbel, Altje L.; Sendow, Greis M. (Indonesian Journal of Applied and Industrial Sciences (ESA), 2024)
This research aims to determine the influence of work performance, work experience and performance evaluation on promotion of employee positions at the North Sulawesi Province Energy and Mineral Resources Service. The sampling method used was a saturated sampling technique with a sample size of 81 respondents. The data analysis technique used is Multiple Linear Regression. The results of this research show that simultaneously, work performance, work experience and performance evaluation have a significant effect on employee promotion at the Regional Energy and Mineral Resources Service of North Sulawesi Province. However, if viewed partially, only performance evaluation has a significant positive influence on employee promotions. Work performance has an insignificant positive effect on employee promotion. Meanwhile, work experience does not have a significant influence on the promotion of employee positions at the Regional Energy and Mineral Resources Service of North Sulawesi Province.